EKSISTENSI HUKUM ADAT DALAM SISTEM HUKUM DI INDONESIA - Eka Susylawati (Faculty of Sharia IAIN Madura collaboration with The Islamic Law Researcher Association (APHI), 2009)
A traditional law (hukum adat) is a law reflecting anIndonesian character; as a result it has been claimed as thelaw which is genuinely Indonesian. As an unwritten law,nowadays the existence of traditional law is questionable.It has been judged as conservative, stiff, primitive oldfashioned comparing to the development of modernsociety. Some people argue that traditional law is unableto resolve the problems in this globalization era. In facts,traditional law has become a basic principle to legalize thecontemporary laws. For instances, traditional lawsinspires the law of UU. No 5 Th. 1960 about the major lawof agrarian affairs and the la of UU. No. 1 Th. 1974 aboutmarriage. The relevance of traditional law to current one issupported by the existence of UU. No. 4 Th. 2004 aboutthe authority of judicial affairs, it opens the chance for thejudges to execute and decide a case based on traditionallaws.